Activity Test of Matoa Leaves on Angiotensin II as an Increasing SOD and GPx - Octaviana Dyah Oentari; Jason Merari Peranginangin; Ika Purwidyaningrum (Journal of Advances in Medicine and Pharmaceutical Sciences, 2024)
The leaves of the matoa are plants that can be used for hypertension. Matoa leaves were assume to have thought to have hypertensive activity because they contain flavonoids (quercetin-3-O-rhamnosida). Flavonoids can lower blood pressure which is modulated by the Renin-Angiotensin-Aldosterone System (SRAA). Was to fine out about the giving process of matoa leaf extract and fractions in increasing levels of SOD and GPx. This research used the maceration method with 96% ethanol solvent and fractionated by liquid-liquid method using n-hexane fraction solvent, ethyl acetate fraction, and water fraction. In this study, 21 male white rats with Wistar strain were divided into 7 groups, group I named as normal control, group II as negative control (CMC-Na 1%), group III as positive control (Irbesartan), and Group IV. (matoa leaf extract), Group V (n-hexane fraction group VI (ethyl acetate fraction) group VII (water fraction). The data obtained were analyzed with the Shapiro Wilk test, Levene's test and ANOVA. The results showed that the matoa leaf extract a dose 300mg/kg BB lower blood pressure in angiotensin II induced rats incrase SOD and GPx levels in the liver induced by Angiotensin II.